Content Analysis of Financial Crisis Articles in Journal of “Türkiye Günlü?ü” - Köse, Dilsad Türkmenoglu (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2024)
The 1980s marked a period when Türkiye made significant strides toward establishing a free market economy and democracy. Until 1980, Türkiye adhered to an economy guided by import substitution development policies. However, with the enactment of the 1982 constitution, following the coup, a transition to a free market economy was initiated. After 1980, one of the most prominent intellectual journals emerging alongside democratization efforts was Türkiye Günlü?ü. This study focuses on articles published in Türkiye Günlü?ü concerning economic transformations, with a particular emphasis on global economic crises. The journal, which began publication after 1980 and continues its activities today, is analyzed using historical-descriptive content analysis. Within this framework, the study aims to clarify the journal’s perspective on Türkiye's economy during the transition to a free market system and in subsequent years.